Wastewater Treatments Based on Adsorption, Catalysis, Biodegradation, and Beyond (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The ongoing technological advancements and industrial growth over the past few decades have arisen significant environmental challenges, particularly the issue of water pollution caused by the improper disposal of organic and inorganic pollutants. Protecting the environment is essential for creating a sustainable future, leading researchers and the public to focus on innovative remediation strategies. As a result, the development of new “green”-oriented, low-cost, and efficient materials for environmental remediation, especially for the removal of pollutants from water bodies, remains a vibrant area of research. The 14 original research articles and two review papers included in this Special Issue aim to explore new methods beyond sorption, biodegradation, and catalytic degradation while also introducing new materials and composites for effective (waste)water treatment and purification.